Relationship of complementary breastfeeding with the nutritional status of infants aged 6-12 months in the working area of the Kolaka District Health Center in 2023 - Ahmad, Amina; Masita, Syarifah; MS, Nurhidayah; Aotari, Wanti (Barongko: Jurnal Ilmu Kesehatan, 2023)
ABSTRACT Giving breast milk alone after the baby is 6 months old is not enough to meet all the baby's food needs because breast milk will only meet 60-70% of the baby's needs, while 30-40% must be met by giving MP-ASI to meet nutritional needs other than breast milk. This study aims to determine the relationship between giving MP-ASI and the nutritional status of babies aged 6-12 months in the working area of the Kolaka City Health Center in 2023. The type of research used is observational analytics with a cross sectional approach carried out in September-October 2020. The number of samples in the study There were 58 respondents where the sample was taken by purposive sampling. The research results based on the chi-square test ρ(0.047) < α(0.05) concluded that Ho was rejected and Ha was accepted, indicating that there was a relationship between the age at which MP-ASI was first given and the nutritional status of babies aged 6-12 months. The results of the chi-square test ρ(0.015) < α(0.05) concluded that Ho was rejected and Ha was accepted, indicating that there is a relationship between the frequency of giving MP-ASI and the nutritional status of babies aged 6-12 months in the working area of the Kolaka Regency City Health Center in 2020. It is hoped that The health service as a related institution can increase education about the correct provision of MP-ASI regarding the age at which MP-ASI is first given and the frequency of MP-ASI administration so that the baby's nutritional needs are met so that the baby can have a normal nutritional status.